Seasonal dynamics of stomach contents, trophic level, length-weight relationship and condition factor of Mystus bleekeri (Day, 1877) - Mazumder, Sabuj Kanti; Kunda, Mrityunjoy; Iqbal, Mohammed Mahbub; Basak, Lipi Rani; Simon Kumar Das, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Asian catfish Mystus bleekeri is a popular food fish along with favored as an ornamental fish in Bangladesh. Till now detailed report on stomach contents, trophic level, length-weight relationship and condition factor of this fish species in the agro-climatic context of Bangladesh is lacking. Hence, the aims of this study were to describe the stomach content, trophic level, length-weight relationship (LWR) and condition factors of Mystus bleekeri collected from Dekhar Haor, Sylhet, Bangladesh from July 2017 to June 2018. A total of 600 specimens ranging from 6.9-24.6 cm total length (TL) and 5.7-72.4 g body weight (BW) was analyzed in this study. Stomach content analysis showed that the fish fed mostly on Mollusca with a frequency of occurrence (fo : 25.36%) and worms (fo : 21.68%), followed by plant matters (fo : 3.32%), Cladocerana (fo : 1.18%), Copepoda (fo : 0.95%), and Teleostei (fo : 0.36%). The estimated mean trophic level (TROPH) ranged from 2.35±0.13 in December to 3.02±0.23 in August, indicating that they are opportunistic feeder. The LWR analysis showed negative allometric growth (b<3) throughout the year. The values of the exponent b in the LWR (W=aLb ) vary between 1.474 and 2.490. The mean K value was significantly higher in October indicating the heavier weight and better condition of the fish (P<0.05). The data obtained from this study would be useful to introduce sustainable management of Mystus bleekeri not only in Dekhar Haor but also in other inland waters of Bangladesh.